L'apporto della linguistica interazionale alla ricerca sui consumatori. La presa di decisione nei punti vendita - De Stefani, Elwys (My University, 2006)
Consumer behavior has traditionally been studied by marketing researchers, who often understand decision making as a result of a subjective assessment process determined by consumer’s intentions. In this paper it will be argued that the description of informal decision-making sequences cannot solely rest on concepts such as intention or intentionality as used in traditional pragmatics, because they are hardly observable on the basis of ethnographically collected data. Instead I propose a conversational approach to consumer behavior showing how social actors employ verbal resources within a space they structure with gestures and movements of their bodies. Particular attention will be drawn to the manipulation of the products to which the decision-making sequences relate. The proposed analysis will permit to distinguish five phases that structure a decision-making sequence in an informal environment.
Keywords: interaction; consumers; decision making; conversation analysis; object manipulation